Earnings at Risk para as instituições não-financeiras e as exigências da lei americana Sarbanes-Oxley - Ferreira, Igor Rocha (2005)
The demand for the corporative responsibility never was so great. The necessity to tie completely the corporative governance with the efficient activities of control never was so clear. This dissertation has the objective to answer the question whether Top Down1 approach of the Earnings at Risk2, might be considered compliant with the Sarbanes-Oxley requirements as a preventive control, and additionally, as an efficient method of risk management for non financial companies. Based on the results we have reached, the Top Down approach of EaR does not address the demands imposed by SarbanesOxley. Although SOX focus in the effectiveness instead of the efficiency of the controls used by the companies, management decision, based on this method may drive the company to big mistakes.